Courting innovation: The effects of litigation risk on corporate innovation - Hassan, M. Kabir; Houston, Reza; Karim, M. Sydul (Journal of Corporate Finance, 2021)
In this study, we examine the impact of class action litigation shocks on corporate innovation. Our experimental design is based on an unanticipated court ruling that reduces the risk of shareholder class action lawsuits for firms located within the jurisdiction of the US Ninth Circuit. Innovation output by firms headquartered in this area increased significantly after this decision compared with that of firms elsewhere. This result is consistent with our trading hypothesis, which states that the threat of litigation leads to managerial myopia. The increase in innovation is more pronounced at high-tech firms and firms operating in a competitive environment. Other measures of ex ante litigation risk indicate that firms with the greatest litigation risk experience the greatest increase in innovation after this decision. We conclude that a reduction in the threat of class action litigation leads firms to increase innovation.